MIC-Net: multi-scale integrated context network for automatic retinal vessel segmentation in fundus image - Jinke Wang; Lubiao Zhou; Zhongzheng Yuan; Haiying Wang; Changfa Shi (Mathematical Biosciences and Engineering, 2023)
Purpose: Accurate retinal vessel segmentation is of great value in the auxiliary screening of various diseases. However, due to the low contrast between the ends of the branches of the fundus blood vessels and the background, and the variable morphology of the optic disc and cup in the retinal image, the task of high-precision retinal blood vessel segmentation still faces difficulties.